1997
DOI: 10.1021/es960883n
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on the Microbial Degradation of Exxon Valdez Oil on the Shorelines of Prince William Sound, Alaska

Abstract: Biodegradation was a major mechanism for removing oil resulting from the Exxon Valdez oil spill in Prince William Sound, Alaska. For three field seasons, we examined the hexadecane, phenanthrene, and naphthalene mineralization potentials of hydrocarbon-degrading microorganisms and the accompanying hydrocarbon concentrations from intertidal and shallow subtidal sediments. We found that mineralization potentials were not directly dependent on sediment substrate concentrations, but environmental factors influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…For instance, it was observed that factors including the intensity of physical mixing, the pre treatments (for example shore washing, manual removal, manual raking, bioremediation using biostimulation agents, mechanical tilling, mechanical relocation), and the availability of alternative carbon sources influenced the mineralization potential of the microbes after the Exxon Valdez oil spill (Sugai et al 1997). Another parameter that has a considerable effect on biodegradation is temperature, due to its effect on the viscosity, water solubility and chemical composition of the oil.…”
Section: Biostimulationmentioning
confidence: 99%
“…For instance, it was observed that factors including the intensity of physical mixing, the pre treatments (for example shore washing, manual removal, manual raking, bioremediation using biostimulation agents, mechanical tilling, mechanical relocation), and the availability of alternative carbon sources influenced the mineralization potential of the microbes after the Exxon Valdez oil spill (Sugai et al 1997). Another parameter that has a considerable effect on biodegradation is temperature, due to its effect on the viscosity, water solubility and chemical composition of the oil.…”
Section: Biostimulationmentioning
confidence: 99%
“…The presence of HDB community in a remote location not previously exposed to fossil hydrocarbons is associated to the presence of biowaxes derived from vascular plants and other terrestrial carbon sources. The coincidence between high C18 mineralisation rate and the presence of high concentrations of C25+C27+C29+C31 alkanes in some reference and oiled bays of the Prince William Sound (60 30 0 N; 147 05 0 W) suggested that terrestrial biowaxes pre-conditioned the microbial populations for an efficient degradation of oil-derived alkanes (Sugai et al, 1997). A recent work conducted in Terre Adelie (Delille, Basse`res, & Dessommes, 1997) showed a significant response of the Antarctic sea-ice HDB community to the addition of oil and fertilizers to newly formed seaice.…”
Section: Bacterial Activitymentioning
confidence: 99%
“…The intricacy of interactions shown to influence the success of bioremediation in this study is not unique. Within the sediments of Prince William Sound, Alaska [70], the ability of the indigenous microbial population to mineralize hexadecane, phenanthrene, and naphthalene, has been shown to be influenced by the intensity of physical mixing, the method of bioremediation agent application, and the availability of alternative carbon sources. The efficacy of specific bioremediation formulations may be influenced by environmental conditions.…”
Section: The Influence Of Oil Chemistry and Environmental Factorsmentioning
confidence: 99%